Flexural strength of notched concrete beam filled with alkali-activated binders under different types of alkali solutions. (30th November 2016) - Phoo-ngernkham, Tanakorn; Hanjitsuwan, Sakonwan; Suksiripattanapong, Cherdsak; Thumrongvut, Jaksada; Suebsuk, Jirayut; Sookasem, Sermsak
Highlights: Sustainable repair binding material using waste materials. Role of GBFS content and kinds of alkaline solutions on bonding strength. FA + GBFS activated with SHSS solution give highest flexural strength of notched PCC beam. SHSS provided high flexural strength of notched PCC beam than those of SH and SS. Abstract: This article investigates the flexural strength of notched Portland cement concrete (PCC) beams filled with alkali-activated binders (AAB). The low calcium fly ash (LFA) and ground granulated blast furnace slag (GBFS) are used to develop AAB. The bond strength performance between notched PCC beam and AAB has been studied. A different mix of AABs were investigated: those are low calcium fly ash (LFA) paste, FA + GGBS paste and GGBS paste with three different types of alkaline solutions viz., 10 M sodium hydroxide solution (SH), sodium silicate solution (SS), and 10 M sodium hydroxide mixed with sodium silicate solution solutions (SHSS). The flexural strength of notched PCC beams filled with AABs at different influence factors are tested under three point bending. Test results evident that the flexural strength of PCC notched beams tends to slightly increase with increasing of GBFS content for all kinds of alkaline solutions. The fracture surface of specimens is reasonable to bond strength obtained. The notched PCC beams filled with FA + GBFS activated with SHSS solution provides the highest 28-day flexural strength of 3.57 MPa. This research attempts to use waste materials as a promoter in AAB as an alternative repair material, which is significant in addressing the sustainable use of waste materials in terms of engineering, economical and environmental perspectives.